Anatomical variations in lung fissures leading to supernumerary lobes in the lungs - K.S. Mpolokeng; M.Y. Madolo; G.J. Louw; G. Gunston (Elsevier, 2022)
Introduction: Lung fissures are partially incomplete in 50% of different populations. Incomplete formation of the fissures leads to a merging of lobes and conversely accessory lobes form due to the formation of new fissures. This study aims to describe the morphology of the lungs in terms of fissures and lobes. Materials and methods: A descriptive observational study was done on a total of 82 formalin fixed bodies. Both the left and right lungs of each body were examined for accessory lobes and fissures. Results: A wide range of variations was seen in the present study. On the right, the horizontal fissure was absent in six lungs (7.3%), incomplete in 32 lungs (39.0%) and complete in 33 lungs (40.2%). No lungs had an absent oblique fissure. The oblique fissure was incomplete in 24 lungs (29.3%) and complete in 47 lungs (57.3%). No right lung solely had an oblique fissure absent. However, both the horizontal and oblique fissures were absent in one lung (1.2%). In the left lungs, the obliques fissure was absent in one lung (1.2%), incomplete in 24 lungs (29.3%) and complete in 47 lungs (57.3%). An accessory fissure was seen in the territory of the upper lobe forming a partial separation in the right superior lobe of one lung. Conclusion: The high prevalence of morphological variations in this study emphasizes the need for greater understanding of lung fissure anatomy. For example, in video-assisted thoracoscopic surgery lobectomies, higher morbidity in patients is linked with incomplete fissures [12]. Thus, more knowledge of lung fissure and lobe variations will be of significant clinical relevance to anatomy students, cardiothoracic surgeons, and radiologists.